Combined use of drug treatment and Reiki therapy in patients with post-traumatic stress pain (Research, Society and Development, 2021)
The use of Reiki has been growing in recent times, being a Japanese technique consisting of na energy therapy. The aimisto analyze the efficacy of the association of Reiki with drug therapy in patients with pain and observe how this treatment canal leviate the symptoms. Thisis a systematic review conducted on the basis of randomized clinical trials. A research was carried out at the Medical Publisher Virtual Health Library. To search the articles, the Descriptors in Health Sciences in the English language were used by the Booleand escriptor AND: Reiki and Pain. Thus, the 5 articles were classified according to the defined criteria System Classification of Recommendations Evaluation, Development and Evaluation. From the selected studies it was observed that the groupsr anged from 30 to 90 patients, followed by the use of opioids, analgesics and anti-inflammatory drugs for pain relief, associated with Reiki in alternating times ranging from 10 to 30 minutes. Further more, it is induced that the association between these and Reiki therapyh a senhanced the effective ness of decreasing pain, stress, anxiety levels and medication time. In some studies, he also found improvement in vital signs. It was concluded that a Reikit herapy associated with drug therapy, such as analgesics and opioids, has good efficacy in patients with pain, and it’s advantage is evident in it’s use in patients who need analgesia.